Irrigation management in Pakistan mountain environment - Vander Velde, E.J. (International Irrigation Management Institute, 1989)
This paper is a preliminary effort to define the extent of irrigation in Pakistan's mountain regions. Attention is given to some changes already begun in this environment through new irrigation development activities. Important knowledge gaps that need to be filled by more systematic and multidisciplinary research are identified.